Base-Mediated Synthesis of Imines and Amines from N-Phenylureas and Alcohols - Yadav, Dilip Kumar T.; Bhanage, Bhalchandra M. (Synlett, 2014)
A new base-mediated protocol has been developed for the synthesis of imines and amines from N-phenylureas and alcohols under normal air. From the synthetic point of view, the protocol can be considered as an efficient alternative to conventional methods for the synthesis of imines and amines in moderate to excellent yields.
Keywords: imines; amines; oxidations; alcohols; ureas